2023
DOI: 10.3390/insects14110853
|View full text |Cite
|
Sign up to set email alerts
|

Functional Response and Intraspecific Competition of Three Ladybird Species Feeding on Aphids on Goji Berry Plants in Laboratory and Semi-Field Conditions

Pengxiang Wu,
Jia He,
Huan Dong
et al.

Abstract: The aphid, Aphis gossypii Glover, is identified as a significant pest that causes severe damage to goji berries in China. To analyze the ladybird consumption of aphids, the functional responses of three ladybird species, Harmonia axyridis, Coccinella septempunctata, and Hippodamia variegata, and intraspecific competition among ladybird individuals were evaluated under laboratory conditions. Moreover, the practical impact of ladybirds on aphid population reduction was investigated in semi-field conditions. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…To further explore the impact of pollen on N. bicaudus cultivation, this study examined the functional response of N. bicaudus when preying upon T. turkestani in the presence of pollen [ 63 ]. The results showed that the predatory functional response of N. bicaudus to T. turkestani still fits the type II response when provided with C. cyanus pollen, B. officinalis pollen, and C. monnieri pollen, thereby indicating that the addition of pollen did not alter the feeding model [ 64 , 65 ]. This is consistent with a previous study [ 66 ], in which the presence of Typha orientalis pollen did not alter the functional response type of Neoseiulus cucumeris .…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the impact of pollen on N. bicaudus cultivation, this study examined the functional response of N. bicaudus when preying upon T. turkestani in the presence of pollen [ 63 ]. The results showed that the predatory functional response of N. bicaudus to T. turkestani still fits the type II response when provided with C. cyanus pollen, B. officinalis pollen, and C. monnieri pollen, thereby indicating that the addition of pollen did not alter the feeding model [ 64 , 65 ]. This is consistent with a previous study [ 66 ], in which the presence of Typha orientalis pollen did not alter the functional response type of Neoseiulus cucumeris .…”
Section: Discussionmentioning
confidence: 99%
“…The direction and angle of prey are typically perceived with exceptional acuity by predators, facilitating their target localization [45,46]. The rapid prey location recognition based on reference objects in its surroundings is more pronounced in H. axyridis compared to H. variegata [47]. Flight is the predominant mode of locomotion for H. axyridis during foraging, while crawling is the primary means of movement for H. variegata [48].…”
Section: Discussionmentioning
confidence: 99%